2014
DOI: 10.1007/s00894-014-2480-5
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical investigation of hydrogen bonding interaction in H3O+(H2O)9 complex

Abstract: Hydrogen bonding interaction of hydronium ion with water molecules in its first and second solvation shell is studied using density functional theory with B3LYP functional and aug-cc-pvtz basis set. The nature of interaction and contribution from various interaction energies to the binding energy of a complex is studied using many-body analysis approach. The hydrogen bonds between hydronium and water molecules in its first solvation shell are stronger than those between water molecules in its second solvation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 87 publications
(49 reference statements)
0
2
0
Order By: Relevance
“…It is known that for systems whose MBEs converge quickly knowledge about molecular clusters can be systematically extended to bulk systems. Many studies have been reported in the literature investigating OH – (H 2 O) n and H 3 O + (H 2 O) n clusters using both theoretical and experimental ,, approaches. However, a rather small fraction of the theoretical work investigated many-body effects in these clusters. ,,,,,, As a first step toward a quantitative assessment of many-body effects of water self-ions in aqueous systems, we report here an analysis of OH – –water interactions in low-energy isomers of OH – (H 2 O) n clusters, with n ≤ 5.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that for systems whose MBEs converge quickly knowledge about molecular clusters can be systematically extended to bulk systems. Many studies have been reported in the literature investigating OH – (H 2 O) n and H 3 O + (H 2 O) n clusters using both theoretical and experimental ,, approaches. However, a rather small fraction of the theoretical work investigated many-body effects in these clusters. ,,,,,, As a first step toward a quantitative assessment of many-body effects of water self-ions in aqueous systems, we report here an analysis of OH – –water interactions in low-energy isomers of OH – (H 2 O) n clusters, with n ≤ 5.…”
Section: Introductionmentioning
confidence: 99%
“…Along with the interest in cooperativity in triads based on comparison of stabilization energies of triad and corresponding dyads the total interaction energy of a triad and pairwise interaction energies into its structure have been also studied using many‐body interaction energy (MBIE) approach . According to MBIE in an ABC triad the total interaction energy is given with following simplified equation: IEABCtotal=IEABABC+IEBCABC+IEACABC+ΔABC …”
Section: Introductionmentioning
confidence: 99%